(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Hotels heavily depend on automated systems to facilitate efficient core transactions. These systems are expected to be reliable and user-friendly and minimize human errors while encoding data for all transactions. However, there is a problem with the current system in terms of usability and security. Therefore, the goal of Core Transaction 2 is to address these issues by developing a web-based system that is user-friendly for administrators and customers to access, input, process, and manage data. Additionally, this system will prioritize data encryption to ensure the privacy and security of clients. The approach taken allowed the project team to create an improved Hotel Management System. It solved problems in booking, reservations, facilities management, and customer management by eliminating unnecessary processes, resulting in faster and better services for guests. The new feature, Core Transaction 2, will improve consistency and efficiency, leading to productive employees and a better guest experience. The following objectives were achieved as a result of deploying this system, which improved the operations and capabilities of Core Transaction 2. 1. Develop a web-based system that is user-friendly for administrators and customers to access, input, process, and manage data. 2. Integrated transactions into the other modules of the Hotel Management System to provide smooth, accurate, and efficient transactions. 3. Enhanced promotions management by creating new promotions and advertising them through social media to attract potential customers. 4. Enhanced customer management by creating a function that allows the customer to reach out to us with their concerns. 5. Enhanced security by providing data encryption, email verification (OTP) for forgotten passwords, and user authentication. In conclusion, the Hotel Management System - Core 2 presents features that simplify and automate its primary operations and procedures, resulting in efficient management of the hotel’s essential transactions.